PENGARUH PELATIHAN RESUSITASI JANTUNG PARU TERHADAP KESIAPAN SEKAA TERUNA TERUNI DALAM MEMBERIKAN PERTOLONGAN PADA KASUS KEGAWATDARURATAN HENTI JANTUNG - Gede Ngurah (Jurnal Gema Keperawatan, 2019)
Emergency may occur anywhere and anytime. Cardiac Arrest is one of the most life-threatening emergency conditions. The CPR action is an important determinant of survival of cardiac arrest survivors. The purpose of this research is to know the effect of CPR training on the readiness to provide STT relief in cardiac emergency cases in Dawan Kaler Village 2018. This research type is pre experimental with pre-post test approach, and using simple random sampling method with 160 respondents. The instrument used is a questionnaire about the readiness to help victims of cardiac arrest. Data analysis used is univariate and bivariate analysis. The result of the research shows that most of the respondents are female (63.8%), most of the respondents are 17-25 years old (95%), most of them are high school (58.1%), most of them are student (80 , 6%), before CPR training for less ready category (32,5%) and category not ready (67,5%), after CPR training, improvement of readiness to help, category ready (63,8%) and ready category ie 36.3%. Statistical test results using Wilcoxan Signed Rank Test obtained p-value 0.000 alpha (0,05). Conclusion: CPR training can improve the readiness of providing emergency assistance in cases of cardiac arrest. Suggestion: STT works together with related health officers to create a continuous training program so that the future is able to do quick and proper handling to help cases of cardiac arrest emergency..